A novel heat pump system using a multi-stage Knudsen compressor. (December 2018) - Kugimoto, K.; Hirota, Y.; Yamauchi, T.; Yamaguchi, H.; Niimi, T.
Highlights: A novel heat pump system using a multi-stage Knudsen compressor (KC) is proposed. The heat pump is driven by thermal energy, and it is suitable for heat recovery. A 1D model to predict the performance of the heat pump is developed. Number of stages and area of KC to achieve a practical performance are evaluated. Abstract: A novel heat pump system is proposed using a multi-stage Knudsen compressor in the cycle between the evaporator and condenser. The proposed Knudsen heat pump is driven by thermal energy, and it is able to utilize waste heat. There are no moving parts in a Knudsen compressor, leading to several advantages, including a lack of vibration and noise, and high durability. In this study, the configuration necessary to achieve a performance such that it can be used as a practical heat pump (output power ≥1 kW, temperature difference ≥6 K) is considered. The performance of this heat pump is predicted by a one-dimensional analytical model coupled with a simple experimental result. This method is based on our previously constructed method to predict the performance of a multi-stage Knudsen compressor, and the evaporation and condensation and the time variations of temperature in the evaporator and condenser are newly considered. A heat pump with a 30-stage Knudsen compressor using glass-fiber filters with an area of 4.00 m 2 is predicted to generate an output power of 1.27 kW and a temperature difference of 6.00 K.